Evaluation of extraction-oxidation synergistic remediation of contaminated dredged sediment and plant suitability effects - Yang, Wenchao; Liu, Jize; Sun, Yuanshu; Wang, Zhaowei; Han, Chengwei; Han, Jianbo (Frontiers in Marine Science, 2025)
Generally, marine dredged sediments often exhibit co-pollution with heavy metals and petroleum hydrocarbons. This work investigates the extraction-oxidation synergistic remediation treatment of heavy metals (Cu and Pb) and total petroleum hydrocarbon (TPH) in the contaminated dredged sediments. The leachability of heavy metals, the oxidation of TPH, the physicochemical properties of the treated sediment, and the fertility of the treated sediment for barley growth are compared among different combinations of extractants [ethylene diamine tetraacetic acid (EDTA), citric acid (CA) and ferric chloride (FeCl3)] and oxidant [potassium persulfate (K2S2O8)]. The results show that the extraction-oxidation synergistic remediation treatment significantly reduces the Cu and Pb contents. The total removal performances of heavy metals and TPH in the contaminated dredged sediments by each co-remediation treatment group are FeCl3+Ox > EDTA-Ox > CA-Ox. Specifically, FeCl3+Ox and EDTA-Ox achieve the highest removal rates of 91.10% and 96.95% for Cu and Pb, respectively. The extractant affects the activation of K2S2O8 by transition metals, enhancing the removal efficiency of TPH. The EDTA-Ox treatment group demonstrates the optimal treatment efficiency (37.42%) for TPH in the dredged sediment in 30 min. In the barley planting experiment, both shoot and root germinations in the EDTA-Ox treatment group reach their maximum values of 100% and 90%, respectively. Additionally, the CA-Ox treatment group exhibits maximal shoot and root lengths of 11.6 cm and 12.1 cm, respectively. The stress caused by salinity on seeds is also mitigated by the treatment. This study can provide technical support for the beneficial use of the dredged sediment.